Students and internationalization : student mobility in the internationalization processes - Quiroga, Sergio Ricardo (Universidade Estadual de Campinas, 2019)
Internationalization in higher education institutions has traditionally included a broad set of elements such as study programs, teaching and learning, research, institutional arrangements, mobility of students and teachers, cooperation, etc.This research addresses the perceptions of "participation", "stay", "experience" and "culture" of students of the National University of San Luis (UNSL) who participated in the internationalization processes in Colombian, Chilean and Mexican universities during the period 2005-2014. Through interviews, the testimonies of four students who had internationalization experiences and who traveled to foreign university centers were collected.The mobility experience is enriching for students and for their future professional life. The experience of mobility is very strong and impressive in all people and more in the students who aspire to develop a future career in the future, and in this way the training is enriched with these learning in different contexts that entail a whole cognitive and cultural experience.